Morphology and Phylogeny of a new species Pseudocercospora rauvolfiicola on medicinal plant Rauvolfia serpentina from Sonebhadra Forest, Uttar Pradesh, India - Singh, Archana; Singh, Paras Nath; Dubey, Nawal Kishore (Phytotaxa, 2022)
A new species of Pseudocercospora is discovered causing foliar disease on the medicinal plant Rauvolfia serpentina (Apocynaceae) from India. The new species is described and illustrated on the morphology of asexual-morphs, growth characters and multigene phylogeny. Morphologically, new species has similar characters with allied species in Pseudocercospora but differs in having catenate and branched conidia. Phylogenetic analysis using combined LSU, ITS, ACT and TEF1α data supports the isolate to be a new species of Pseudocercospora (Capnodiales, Mycosphaerellaceae).